Batee Sumpah: A Symbol of Sacredness and Its Influence on the Seunebok Padang Community, Teunom, Aceh Jaya - Majid, Abdul; Avafudin, Avafudin (Prodi Studi Agama-Agama, 2025)
The Oath Stone in Seunebok Padang Village, Teunom District, Aceh Jaya, serves as a sacred symbol representing the values of honesty, responsibility, and social balance within the community. This stone functions as a medium for solemn oaths aimed at fostering harmony and strengthening communal unity in peacefully resolving conflicts. However, with the advancement of time and the influence of modernization, the meaning and relevance of this tradition have begun to be questioned, particularly by the younger generation. This study aims to explore how the people of Seunebok Padang perceive the sacredness of the Oath Stone, including its spiritual and symbolic values, as well as the social impact of the associated rituals. A qualitative research methodology with a descriptive approach was employed, incorporating direct observations, in-depth interviews with traditional leaders and religious figures, and documentation of related traditions. The findings reveal that the community interprets the Oath Stone as a moral symbol that emphasizes honesty, responsibility, and the importance of maintaining harmony and justice. The social impact of this ritual is reflected in the preservation of social cohesion and the peaceful resolution of disputes. The continued sanctity of the Oath Stone is upheld as an effort to preserve cultural heritage, which embodies noble values, serves as a guide for life, and reinforces the collective identity of the community.